2021
DOI: 10.3390/agronomy11010176
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Light Interception in Cotton Populations of Different Densities

Abstract: Modification of the cotton canopy results in shade avoidance and competition for light, which shows that density and spatial arrangement of cotton have a great impact on light interception. This experiment was conducted in 2018 and 2019 in the experimental field at the Institute of Cotton Research of Chinese Academy of Agricultural Science in Anyang city, Henan Province, China. Six plant densities of cotton variety SCRC28 were used to assess spatial competition for light in cotton populations during the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Heilman and Namken (1990) noted that the canopy closure of 76-cm rows was nearly 30 days earlier than the canopy closure of 102-cm row spacings. Chen et al (2021) observed that light interception was highest where plant populations were high. Riar et al (2009) noted that narrow 38-cm rows intercepted more light and reached canopy closure sooner than 97-cm rows.…”
Section: Resultsmentioning
confidence: 98%
“…Heilman and Namken (1990) noted that the canopy closure of 76-cm rows was nearly 30 days earlier than the canopy closure of 102-cm row spacings. Chen et al (2021) observed that light interception was highest where plant populations were high. Riar et al (2009) noted that narrow 38-cm rows intercepted more light and reached canopy closure sooner than 97-cm rows.…”
Section: Resultsmentioning
confidence: 98%
“…The source of cotton growth is carbohydrates produced by photosynthesis, and different populations have different light distributions and solar radiation energy utilization [23,24]. There are differences in the characteristic values of dry matter accumulation among different planting densities [25].…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative interception rate and transmittance in the whole canopy was calculated by Surfer software (Golden Software Inc., Golden, CO, USA) using the extended Simpson's 3/8 rule. The formula was as follows [24]:…”
Section: Light Interceptionmentioning
confidence: 99%
“…As an important cash crop, cotton is highly valued by governments worldwide [1][2][3][4]. Xinjiang is the central cotton planting and production area in China.…”
Section: Introductionmentioning
confidence: 99%